Pengaruh Budaya Organisasi Terhadap Semangat Kerja Guru pada MTs Nurul Falah Kamar - Ansori, Putra Budi; Hasana, Maili (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This study aims to determine the effect of organizational culture on teachers' work enthusiasm at MTS Nurul Falah Sibiruang Koto Kampar Hulu. The organizational culture implemented in the school serves as a key factor in fostering a supportive work environment and enhancing teachers’ motivation. This research employs a quantitative descriptive approach. Data were collected through observation, questionnaires, and documentation. The population consisted of all 30 teachers at MTS Nurul Falah, and the sampling technique used was a census. Data analysis was conducted using simple linear regression with the assistance of SPSS version 23. The results revealed that organizational culture has a significant influence on teachers’ work enthusiasm, as indicated by the calculated t-value exceeding the critical t-value at a 0.05 significance level. The coefficient of determination (R²) shows that organizational culture accounts for 49.4% of the variance in work enthusiasm, while the remaining percentage is influenced by other factors not examined in this study. Therefore, it can be concluded that the stronger the organizational culture, the higher the teachers’ work enthusiasm.